MANAGEMENT OF ACUTE PAIN IN PATIENT WITH PATIENT-CONTROLLED ANALGESIA - Siska Permanasari Sinardja; IGN Mahaalit Aribawa (E-Jurnal Medika Udayana, 2013)
Acute and chronic pain each has its own challenges because these patients are often dependent on opioids and have many psychosocial factors. None of these methods of pain control are superior than others. However, one method to gain control quickly to acute pain is to use a patient-controlled analgesia (PCA). PCA is generally assumed that intravenous opioid administration, on-demand, intermittent under the control of patients. There are some advantages and disadvantages of using PCA for acute or chronic pain management. Therefore shall consider pathways, opioid type, dose and dosage regimen initial adjustment, and management of side effects.